Sinosenecio ovatifolius (Asteraceae), a new species from Guangxi, China - Zou, Chun-Yu; Liu, Yan; Liu, Ying (Phytotaxa, 2020)
Sinosenecio ovatifolius (Asteraceae, Senecioneae), a new species occurring in northeastern Guangxi, China, is illustrated and de-scribed with report on its floral micromorphological characters, achene surface feature and chromosome number. The new spe-cies is phylogenetically close to S. guangxiensis, S. jiangxiensis, S. jiuhuashanicus, S. latouchei, S. peltatus, S. saxatilis, and S. wuyiensis. Morphology and sequence divergence of the nrITS region indicate that S. ovatifolius is well differentiated from its close relatives. It most closely resembles S. guangxiensis and S. latouchei in the scapigerous habit, leaf texture and indumentum, but differs markedly in the ovate lamina, inconspicuously undulate-dentate margin and glabrous and smooth achene surface.